Talent management and job satisfaction of medical personnel in Polish healthcare entities - Pomaranik, Wioletta; Kludacz-Alessandri, Magdalena (Frontiers in Psychology, 2023)
Background: There is a mass exodus of qualified medical personnel in countries such as Poland. As a result, it is becoming increasingly important to study the satisfaction of medical personnel employed in public healthcare entities and the factors influencing this satisfaction. One such factor is the quality of talent management. Purpose: The study aimed to assess the quality of talent management in Polish healthcare entities and its impact on the job satisfaction of medical personnel. The study also considered the impact of other demographic, organisational and behavioural factors on medical personnel satisfaction, such as social competencies, job mobility, orientation towards the patient, gender and education stage. Methods: A questionnaire for healthcare professionals was used to collect data. A total of 747 respondents (506 defined as medical talent) participated in the survey. A 5-point Likert scale was adopted to assess job satisfaction and talent management practices. Reliability analysis was conducted to investigate the properties of this scale and the items that comprise it. The data was analysed using descriptive statistics and structural equation modelling. Results: The survey showed that the quality of talent management in Polish healthcare institutions is not well assessed. Professional satisfaction of medical personnel working in Polish public healthcare entities depends mainly on talent management measured by talent motivation, talent development, employee appraisal and organizational culture. Among the factors that have a positive but smaller impact on job satisfaction are job mobility and the education stage. The impact of gender, patient orientation and social competence had the smallest but most significant impact on job satisfaction. Conclusions: Healthcare organisations should improve their talent management strategy to meet healthcare professionals' current and future demands and improve their job satisfaction. Originality/value: This study fills a research gap regarding the impact of talent management on the job satisfaction of talented medical personnel in the context of the healthcare sector.